Polaronic Effects of a Hydrogenic Donor Impurity in Low Dimensional Semiconductor Systems (Journal of Scientific Research, 2009)
The ground state of a polaron bound to hydrogen like donor impurity is investigated by considering the effect of bulk Longitudinal-Optical (LO) phonon. Donor binding energy of a hydrogenic donor, with the inclusion of electron-phonon interaction is computed for the low-dimensional semiconducting systems like quantum well, quantum well wire and quantum dot taking GaAs/AlxGa1-xAs systems as an example. Calculations are performed using a variational approach within the single band effective mass approximation. The results show that the polaronic effect is more pronounced for the lowest confinement. The polaronic effect enhances the donor binding energy but it diminishes when the well width, wire radius and dot radius become larger. Also the numerical calculations reveal that the influences of phonons on donor are considerable and should not be neglected especially for narrow dimensions in all the three confinements.Keywords: Donor binding energy; Polaronic effect; Quantum dot; Quantum wire; Quantum well.© 2009 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved.DOI: 10.3329/jsr.v1i3.2529            J. Sci. Res. 1 (3), 422- 429 (2009)